An experimental study to determine the optimum depth of steel anchors in RC subjected to shear force. (October 2022) - Odacioglu, Orhan Gazi; Dogan, Orhan; Kale, Fulya
Abstract: Unlike existing in-plane strengthening RC shear-walls, anchors are used in strengthening of RC buildings to attach out-of-plane RC shear-walls or steel profiles. It is necessary to know the shear capacity as well as the ductile and nonlinear behavior of the anchor bolts as a connector to be used in the transfer of the shear force between the existing and new elements in strengthening. Considering that the existing RC structures in Türkiye are designed, according to the earthquake codes, with C14 concrete compressive strength until 1998, C18-20 until 2007, C20 until 2018 and also C25 after 2018, knowing the optimum anchorage depth depending on the concrete strength is of great importance in the strengthening analyzes of these structures. In this study, it was aimed to determine the shear performance and optimum anchorage embedment depth of steel sleeve expansion anchor bolts in RC. For this purpose, a total of 72 push-shear tests were conducted on M10 bolts for 6 different classes of low and normal strength concrete and 4 different anchorage depths. As a result of the experiment, it was observed that the shearing capacity of the anchor bolts increased with the increase of concrete strength and anchorage depth. However, for an optimum anchorage embedment depth, it has been observed that the anchor shear capacity reaches the maximum and remains constant without being affected from increment of the embedment depth and the change in concrete strength.